Comparison study on management and marketing strategies case study: Village Mall and Central Square, Sungai Petani, Kedah / Siti Masliana Abd Latip - Abd Latip, Siti Masliana (2010)
Shopping mall management is a profession that had long existed for managing the whole operation of the shopping mall. The main purpose of the shopping mall management is to ensure that the customers of the mall including the tenant can enjoy the service provided optimally. In order to achieve that, the management not only has to provide the best services, but also manage the mall very well and maintain the best condition and always upgrade the atmosphere of the shopping mall to attract the people to come and enjoy while at the mall. As to make the mall successful, the marketing strategies should be the best for long term investment. So, this study focused on how both of the shopping malls carried out their marketing strategies in order to achieve high level of guest's satisfaction. This study was done by interviewing the Event and Operation Manager of Village Mall, Mr Gopinanth and Mr Kim Heong Seng, the Marketing Manager of Central Square shopping mall. The source of data and information has been gathered and collect from many sources such journal, articles, newspaper, opinions from qualified person and questionnaires. By the end of this project, it is hoped that it can clearly explain regarding the management and the marketing strategies of shopping malls.